2013
DOI: 10.1167/iovs.13-12497
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-3 and TNF-α Regulate Retinal Endothelial Cell Apoptosis

Abstract: Taken together, loss of IGFBP-3 signaling results in a phenotype similar to neuronal changes observed in diabetic retinopathy in the early phases, including increased TNF-α levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Thus, our data strongly supports work in other organs that TLR4 can reduce insulin signaling. These data agree with other studies on IGFBP-3 and β-adrenergic receptors, which showed altered insulin signaling, despite normal glucose levels [24, 25]. Further studies on insulin signal transduction and TLR4 will be done once these mice are made diabetic.…”
Section: 0 Discussionsupporting
confidence: 91%
“…Thus, our data strongly supports work in other organs that TLR4 can reduce insulin signaling. These data agree with other studies on IGFBP-3 and β-adrenergic receptors, which showed altered insulin signaling, despite normal glucose levels [24, 25]. Further studies on insulin signal transduction and TLR4 will be done once these mice are made diabetic.…”
Section: 0 Discussionsupporting
confidence: 91%
“…It was postulated that this anti-inflammatory effect may be protective in the setting of diabetic nephropathy, which is supported by a study showing that TNFA, which is proinflammatory, reduced IGFBP3 expression in retinal endothelial cells via activation of p38a MAPK and casein kinase 2 under high glucose conditions . Furthermore, IGFBP3 inhibited whereas TNFA increased retinal endothelial cell apoptosis (Zhang et al 2013c). …”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…However, two other members of the IGFBP family are known to be associated with cytokine production, namely IGFBP3 and IGFBP5. The loss of IGFBP3 was previously shown to be associated with an increase in TNF-α expression, 30 and Ad.IGFBP-3 was found to down-regulate both local and systemic levels of NF-κB-targeted proinflammatory cytokines. 31 Moreover, Lee et al reported that IGFBP3 degrades NF-κB regulatory molecules (IκBα and p65-NF-κB), thereby demonstrating that IGFBP-3R can mediate caspase activation via an IGF-independent mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…28 IGFBP3 and IGFBP5 were already known to suppress the secretion of proinflammatory cytokines by inhibiting the NF-κB signaling pathway. [29][30][31][32] Therefore, we studied whether this signaling pathway is involved in the IGFBP7-mediated suppression of cytokines. After T-cells were cocultured with MSC con , their protein levels of p-p65 and p-IκBα in CD3-T-cells were significantly down-regulated.…”
Section: Igfbp7 Knockdown In Mscs Restores the Proinflammatory Cytokimentioning
confidence: 99%